Barriers and facilitators to the implementation of nutrition interventions at primary health care units of Ethiopia: A consolidated framework for implementation research. Issue 1 (5th October 2022) - Endris, Bilal Shikur; Fenta, Esete; Getnet, Yalemwork; Spigt, Mark; Dinant, Geert‐Jan; Gebreyesus, Seifu H.
Abstract: Accumulating evidence clearly shows poor implementation of nutrition interventions, in Ethiopia and other African countries, with many missed opportunities in the first 1000 days of life. Even though there are high‐impact interventions in this critical period, little is known about the barriers and facilitators influencing their implementation. This paper aims to explore barriers and facilitators for the implementation of nutrition services for small children with a focus on growth monitoring and promotion, iron‐folic acid supplementation and nutrition counselling. We conducted a qualitative study in four districts of Ethiopia. The data collection and analysis were guided by the consolidated framework for implementation research (CFIR). A total of 42 key informant interviews were conducted with key stakeholders and service providers. Interviews were transcribed verbatim and coded using CIFR constructs. We found that from 39 constructs of CFIR, 14 constructs influenced the implementation of nutrition interventions. Major barriers included lack of functional anthropometric equipment and high caseload (complexity), poor staff commitment and motivation (organisational incentive and reward), closed health posts (patient need and resource), false reporting (culture), lack of priority for nutrition service (relative priority), poor knowledge among service providers (knowledge and belief about the intervention) and lack of active involvement and support from leaders (leadership engagement). Adaptability and tension for change were the facilitators for the implementation of nutrition interventions. Effective implementation of nutrition interventions at primary health care units requires several actions such as improving the healthcare providers' motivation, improving leadership engagement, and creating a strong system for monitoring, supportive supervision and accountability. Key messages: Key barriers include lack of resources such as functional anthropometric equipment, high caseload, poor staff commitment and motivation, closed health posts, false reporting and lack of accountability, lack of priority for nutrition services, poor nutrition counselling, and poor leadership engagement and support. Improving implementation of nutrition services requires systematic identification of barriers and designing adaptable solutions. Our study highlights the need for separate growth monitoring and promotion (GMP) rooms and service providers. Service providers need adequate training to provide nutrition services. There is a need for improved monitoring supervision, leadership engagement and regular and improved carrier development and incentives.